Improving the Service Quality In A Board Game Café with Quality Function Deployment Method - Winarto, Mikhael Bima; Wurjaningrum, Febriana (Universitas Airlangga, 2023)
Customers are the most important factor in business because it is undeniable that customers are a source of income and the main goal of business. Given this, an enterprise must pay attention to customer satisfaction for sustainable operations. Enterprises show their concern for customer satisfaction by continuously improving and developing their service processes, as it requires a significant investment, so it should be done following the customer's preferences. Therefore, a business needs to measure customer satisfaction with its service process. This study aims to measure customer satisfaction with the service process and analyze the results of these measurements to provide improvement suggestions for service processes that customers find unsatisfactory. This study also analyzes Green Practice because previous research stated that Green Practice can indirectly increase customer satisfaction with a service. The results of this study indicate that the quality of the board game café services as a whole is still not good. They still need improvement and determine the priority for improving service processes according to the level of customer interest. In addition, customers considered the Green practices of the café to be satisfactory, so it does not require much improvement.